2019
DOI: 10.3390/f10010058
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Road Density, Urban Forest Landscapes, and Structural-Taxonomic Attributes in Northeastern China: Decoupling and Implications

Abstract: A better understanding on the associations between road density (RD), urban forest structural-taxonomic attributes, and landscape metrics is vital for forest ecological service evaluations and suitable management in sprawling urban areas with increasing road networks. We chose Harbin, a fast growing provincial capital city in northeast China, as a case study to address this issue. We utilized ArcGIS software (Esri, version 10.0; Redlands, CA, USA) and FRAGSTATS (V4.2.589) to digitize GF-1 images (Gaofen No.1 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Large inter-site variations in the shelterbelt-induced soil changes were found ( Figure 2 and Table A1 ). Currently, global climatic changes strongly affect local development including natural processes in farmlands, pastures, and forests (Li, 2000 ; Li Y. et al, 2018 ) and new developments has been reported in tree inventory methods (Wang et al, 2018a ) and complex association analysis (Lv et al, 2018 ; Wang et al, 2018b ; Yang et al, 2019 ). Decoupling the contribution of different components on inter-site variations of the shelterbelt-induced soil changes will favor the mechanical understanding of underlying processes, and is a possible strategy for large scale evaluation of shelterbelt poplar ecological functions (Wang et al, 2018b ; Yang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large inter-site variations in the shelterbelt-induced soil changes were found ( Figure 2 and Table A1 ). Currently, global climatic changes strongly affect local development including natural processes in farmlands, pastures, and forests (Li, 2000 ; Li Y. et al, 2018 ) and new developments has been reported in tree inventory methods (Wang et al, 2018a ) and complex association analysis (Lv et al, 2018 ; Wang et al, 2018b ; Yang et al, 2019 ). Decoupling the contribution of different components on inter-site variations of the shelterbelt-induced soil changes will favor the mechanical understanding of underlying processes, and is a possible strategy for large scale evaluation of shelterbelt poplar ecological functions (Wang et al, 2018b ; Yang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…To identify the possible contributions from climatic conditions, soil texture, and tree growth that affected soil property changes following afforestation, statistical methods including RDA and stepwise regression analysis were applied, which have been proven as beneficial for determining the causal relationship between patterns (Eisenhauer et al, 2015 ; Wang et al, 2018b ; Yang et al, 2019 ). Accordingly, we found that the inter-site variations in the shelterbelt-induced soil changes in surface soils were different from those in deeper soils.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also show that fast urbanization in China strongly increased forest soil carbon sequestration at urban center (Zhai et al 2017;Lv et al 2018), possibly owing to soil fungal-related carbon and soil carbon turnover rate (Wang et al 2019b(Wang et al , 2020. Landscape-level configuration could improve forest ecosystem stability and favor tree growth and carbon sequestration (Zhang et al 2017a, b;Yang et al 2019;Zhao et al 2016).…”
Section: Forest Carbon Sequestrationmentioning
confidence: 99%
“…However, the ecological effects of roads are many times wider than the road itself and can be immense and pervasive [ 11 ]. Because of the broad landscape context of road systems, it is essential to incorporate landscape patterns and processes in the planning and construction process [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This provides for the development of a more integrated land use strategy by taking into account different land management practices and prioritization of habitat conservation concerns [ 20 , 21 ]. The mentioned approach promotes a more integrated, larger scale methodological procedure that contemplates landscape patterns and processes in the planning of transportation infrastructure [ 4 , 16 ].…”
Section: Introductionmentioning
confidence: 99%